Calcium Signaling - Islam, Md. Shahidul (Advances in Experimental Medicine and Biology, 2012)
This volume contains a unique selection of chapters covering a wealth of contemporary topics in this ubiquitous and diverse system of cell signaling. It offers much more than the accessibility and authority of a primary text book, exploring topics ranging from the fundamental aspects of calcium signaling to its varied clinical implications. It presents comprehensive discussion of cutting-edge research alongside detailed analysis of critical issues, at the same time as setting out testable hypotheses that point the way to future scientific endeavors. The contributions feature material on theoretical and methodological topics as well as related subjects including mathematical modeling and simulations. They examine calcium signaling in a host of contexts, from mammalian cells to oocytes, zebrafish and plants. With much of interest to newcomers to the field as well as seasoned experts, this new publication is both wide-ranging and authoritative.